Stem Cell-Based Approaches for Spinal Cord Injury: The Promise of iPSCs - Chih-Wei Zeng (Biology)
Spinal cord injury (SCI) is a life-altering condition that leads to severe neurological deficits and significantly impacts patients’ quality of life. Despite advancements in medical care, current treatment options remain largely palliative, with limited ability to promote meaningful functional recovery. Induced pluripotent stem cells (iPSCs) have emerged as a promising avenue for regenerative medicine, offering patient-specific, cell-based therapeutic potential for SCI repair. This review provides a comprehensive overview of recent advancements in iPSC-based approaches for SCI, detailing the strategies used to generate neural cell types, including neural progenitor cells, oligodendrocytes, astrocytes, and microglia, and their roles in promoting neuroprotection and regeneration. Additionally, we examine key preclinical and clinical studies, highlighting functional recovery assessments and discussing both standardized and debated evaluation metrics. Furthermore, we address critical challenges related to safety, tumorigenicity, immune response, survival, integration, and overcoming the inhibitory microenvironment of the injured spinal cord. We also explore emerging approaches in biomaterial scaffolds, gene editing, and rehabilitation strategies that may enhance the clinical applicability of iPSC-based therapies. By addressing these challenges and refining translational strategies, iPSC-based interventions hold significant potential to revolutionize SCI treatment and improve outcomes for affected individuals.